Ketimpangan Pelayanan Kesehatan Sebagai Faktor Determinan Stunting: Studi Perbandingan Antara NTT Dan DKI Jakarta - Siti Sofiaturrohmah; Andi Kasman; Raga Andika Mahasin (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2025)
This study aims to analyze healthcare service disparities as a determinant factor of stunting in Indonesia, focusing on comparisons between East Nusa Tenggara (NTT) and Jakarta. The research employs a comparative qualitative-quantitative approach, utilizing secondary data collected from official sources such as BPS, Riskesdas, government reports, and scholarly articles. The sample includes national and regional statistical data derived from health surveys and health facility reports. Data analysis involves triangulation and applies the interactive model developed by Miles and Huberman to explore relationships between access, quality, and health outcomes related to stunting prevalence. Key findings reveal that limited access and poor quality of health services in NTT contribute to a high prevalence of stunting, whereas Jakarta benefits from comprehensive facilities and adequate healthcare resources, resulting in lower stunting rates. The study concludes that improving health infrastructure, distributing healthcare personnel, and enhancing nutrition education in underserved areas are crucial measures. Recommendations include strengthening regulations, fostering cross-sector collaborations, and implementing minimum service standards to reduce disparities and significantly decrease stunting rates. The findings emphasize the importance of targeted interventions in remote regions to achieve equitable healthcare services across Indonesia.